Organizational Justice and Flexible Work Arrangement: Equating Generation Y’s Motivation Towards Precarious Work Behaviour - Alisa Hussain, Ibiwani; Amir Ishak, Noormala; Hussein, Norashikin; Fazilah Hamid, Siti (International Journal of Engineering and Technology, 2026)
It is interesting to unfold factors that motivate the new generation’s work approach. To-date, among the renowned way of work is precarious work behavior and scholars have distinguished a few factors associated with it. Precarious work behavior is a type of employment that is uncertain, unpredictable and often triggers unpleasant events which may lead to enhanced debts. The study is intended to examine the influenced of organizational justice and flexible work arrangement on precarious work behaviour among Gen Y in Malaysia. This is a quantitative study and primary data were collected through online survey with a total of 179 respondents participated. In addition to descriptive and frequency analysis, correlation analysis and multiple regression were also employed to ascertain the contribution of the study. Findings revealed that in the context of Malaysian’s Gen Y, both organizational justice and flexible work arrangement are significantly related with precarious work. While between the two factors, it was discovered that organizational justice described more on the intention to perform precarious work compared to flexible work arrangement.
Keywords: Organizational Justice; Flexible Work Arrangement; Precarious Work Arrangement; Gen Y.